STRATEGI PENGURANGAN KETIDAKPASTIAN DALAM SISTEM KOMUNIKASI INTERPERSONAL (Studi Fenomenologi pada Peserta On The Job Training Program Ke Jepang dari PT. Hitachi Construction Machinery Indonesia Periode Pemberangkatan Tahun 2009-2012) - Nurvita Wahyu Febriani (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
As a social human and God’s creature, people interacting with others through human communication (interpersonal communication). Interpersonal communication generally involves two people whose communicate each other, whether they already knew or never known each other. Berger and Calabresse (in West and Turner, 2013: 174) believed it is natural to have doubts about our ability to predict the outcome of initial encounters. He is also argued that the beginnings of personal relationships are fraught with uncertainties and communication becomes the primary method to reduce these uncertainties.On The Job Training Program is a program that was organized for the subsidiaries of Hitachi Construction Machinery (HCM) Group that is in some countries such as Indonesia, Russia, China, Malaysia, etc. Since they start of the program in Japan, the participants especially from PT. Hitachi Construction Machinery Indonesia feel the differences such as the work climate, culture, and the personal character of the Japanese people. These differences make the participants feel the uncertainty. By applying Uncertainty Reduction Theory, this research is aim to examine uncertainties perceived by the participants On The Job Training Program of PT. Hitachi Construction Machinery Indonesia, especially in their interpersonal communication activities with other participants from Japan. In addition, this research aims to examine participant strategies to reduce these uncertainties.